Application of Dendrocalamusasper (Schult.) Backer (Buluh Betong) with the combination of bamboo biochar and edta in phytoremediation - Nur Syazwani, S; Mokhatar, SJ; Abas, NA; Yong, JWH; Khairil, M (Forest Research Institute Malaysia, 2024)
Phytoremediation technology utilises the ability of plants to remove metal toxicity in the soil. Bamboo is one of the fast-growing woody plants that may potentially facilitate the immediate removal of toxic metals from the soil. This study was conducted to identify the potential of Dendrocalamus asper in phytofiltering metal elements from the mining sites such as the Chini watershed in Pahang. Dendrocalamus asper was grown in a greenhouse with several applications of bamboo biochar (BB) and EDTA in addition to the efficiency test in reducing soil contaminants for 100 days. The present study found Dendrocalamus asper with the addition of BB+EDTA had reduced 37.44% Fe, 43.72% As, 79.27% Pb, 22.67% Cd, and 48.60% Al concentration in the soil. The same treatment also showed a higher plant accumulation of metal concentrations Pb (31-fold) followed by Al (1.3-fold), Cr (1.3-fold), As (1.05-fold), Fe (82%) and Cd (81%) compared to the control. Growing bamboo with the combination of BB+EDTA was found to be useful for Pb phytoextraction and suitable as a phytostabiliser for Al, Fe, As, Cr and Cd. The understanding in the potential of Dendrocalamus asper in reducing soil contaminants may benefit stakeholders in managing and restoring contaminated sites in the future. © Forest Research Institute Malaysia.